The energy cost of swimming and its determinants - Zamparo, P.; Gatta, G. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The energy cost of swimming (C) is defined as the energy expended to cover a given distance: to reach fast speeds C should be reduced, as much as possible. C depends on hydrodynamic resistance (Wd: the lower the better), propelling (Eta p) and overall (Eta o) efficiency (the larger the better); unfortunately, these parameters are quite difficult to measure in water and the methods proposed so far in the literature to assess/calculate them yield very different results. It is thus necessary to understand, first of all, which values of Eta p, Eta o and Wd are "reasonable" and which are not. Recent evidence (in front crawl swimming) indicates that active drag (Wd) is 1.5 times larger than passive drag, Eta p is of about 0.4 and Eta o is of about 0.2. If these values are indeed "reasonable", it should be possible to estimate C "going up the efficiency cascade". Examples of these calculations, based on data collected on elite sprinters and long distance swimmers, are reported and discussed. These examples show that our knowledge of the determinants of the energy cost of swimming is, nowadays, indeed "quite reasonable".